PROSES PEWARISAN BUDAYA ANYAMAN MASYARAKAT ALUNE DI NEGERI RIRING - Korlina Makulua (Institut Agama Kristen Negeri (IAKN) Ambon, 2021)
The inheritance of local culture is something that must be done considering the development of science and technology that is growing. If the inheritance of local culture is not carried out properly, it is feared that local culture will be increasingly eroded and will gradually disappear from the people who use that culture. The Alune people in the Riring country are also temporarily passing on the woven culture to the younger generation of Alune. The process of inheriting the woven culture in the country of Riring is carried out in two ways, namely through informal and formal educational institutions. Through formal educational institutions, namely by including local content in the school curriculum. Through this method, children are expected to learn about the woven culture. Meanwhile, through informal educational institutions, the process of inheritance of woven culture is carried out by direct involvement, without being limited by space and time. This method is considered quite effective because it is carried out in a comfortable and relaxed atmosphere without any coercion, but is carried out voluntarily so that people who experience this process will feel comfortable and in the end will have an impact on their knowledge and skills in making plaits.It is hoped that all parties in the community will continue to make various breakthroughs in maintaining and inheriting local culture including the almost extinct woven culture among the younger generation of Alune people.